PENURUNAN KADAR RHODAMIN B DALAM AIR LIMBAH DENGAN BIOFILTRASI SISTEM TANAMAN - Purnamawati, K. Yogi; Budiarsa Suyasa, IW.; Mahardika, IG. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2015)
The textile industry is growing rapidly and as the result it’s producing waste that can harm the environment. One of which is rhodamine B. Rhodamine B is a synthetics dyes that have a form crystalline which an organic base containing amino groups, so it is difficult to degrade naturally by microorganism. Biofiltration system method is one of many ways in handling wastewater. Layered filtration unit of sand and rocks combine with the adsorption of plant and decomposition by microorganisms in rhizosphere so that wastewater can be reused. The aim of this study determined effectiveness and capacity of biofiltration system vegetation in reducing concentrate of rhodamine-B, total dissolved solid (TDS), total suspended solid (TSS) and the pH in wastewater. The result showed that biofiltration effectiveness in reducing rhodamine B, TDS and TSS concetrate were 51,70%; 47,60%; 50,44% while decreasing and stabilization of pH obtained at 30 hours treatment time with pH value is 7,5. Capacity of biofiltration system vegetation with volume 0,06 m3 can reduced rhodamine B, TDS and TSS by 0,2256 ppm; 278,0237 ppm and 9,4978 ppm respectively, while the optimum detention time of wastewater in the biosystem for reducing rhodamine B was 30 hours and for TSS and TDS was 36 hours. It can be concluded that biofiltration system vegetation was able to reduce rhodamine B, TDS, TSS and pH of wastewater
Keywords: Biofiltration System Vegetation; Rhodamine B; Effectiveness; Capacity